Analysis of Implementing Core Moral Values on Employee Work Motivation in the Main Directorate PT. Pupuk Sriwidjaja Palembang - Rahman, Raden; Fauzan Azhmy, Muhammad; Syahyunan, Syahyunan (Sumber Belajar Sejahtera, 2025)
This study aims to analyze the implementation of moral core values in employee work motivation at the Main Directorate of PT PSP. The research method used is qualitative with a descriptive approach. Data were obtained through observation, in-depth interviews, and document analysis. The results showed that implementing AKHLAK core values is important in increasing employee work motivation. Employees who internalize moral core values tend to be more dedicated, have integrity, and collaborate. The practical implication of this research is the need for companies to strengthen the implementation of AKHLAK core values in organizational culture to improve employee performance.